(untitled) (A+BE | Architecture and the Built Environment, 2014)
‘The joint residents’ initiative aimed at renewable energy optimization has been increasing in The Netherlands. This is evident from the survey carried out for this study during 2012 of ‘renewable energy residents initiative’ in The Netherlands, as well as the changing government policy. The engineering sector is contributing to this development by introducing new types of energy systems for housing complexes with multiple households. The underlying reasons for this change are the societal change towards less government involvement and the increase of civilian initiative in society. The underlying reason is the disappointing outcome of the current energy program, referring to the monitoring of the ‘Central Planning Bureau’ (CPB, 2009), and the ‘Energy Research Centre of The Netherlands’ ( ECN, 2010). The agreements with third parties, housing associations and developers did not result in the required and desired results (Ministry VROM & NEPROM, 2008) (Ministry VROM & Aedes, 2009). The task of the governmental program ‘Clean and Efficient ‘ for the ‘ urban environment’ is daunting (Ministry VROM, 2007a). Before 2020, CO2 emissions must (with 1990 as reference) be reduced by 30 %. Renewable energy share will have to contribute 20% to this decrease (in the less stringent ‘Energy Agreement’ (Ministry EZ, 2013) this contribution of renewable energy has remained unchanged unless the new 14% target for 2020). This is in accordance with the restated agreements with the rental sector and project development entrepreneurs (Ministry BZK & Hire Partners, 2012) (Ministry BZK & Partners, 2012). This is further supported by recent government policies. In 2011, the government developed, the ‘Plan for energy saving within urban environment‘ (Ministry BiZa, 2011b), including the ‘Block for Block’ program (Ministry BiZa, 2011a) which was aimed at reducing the energy consumption on the basis of clusters of homes. In addition, the program ‘Promoting Renewable Energy’ ( SDE ) emerged during this period and the subsequent ‘National Energy Agreement for Sustainable Growth’ (hereinafter called the ‘Energy Agreement’) (Ministry EZ, 2013 ) which are focusing on the achievement of the national goals for renewable energy emphasizing on citizen participation and initiative. However, in practice there is no breakthrough in this field: the inventory of ‘joint residents initiative’ for ‘renewable energy’ conducted in 2012 showed that only 0.2 % of Dutch households are involved. This result is consistent with the conceptual model of the ‘Transition Theory‘ ( Rotmans, 2003) (Rogers 2003). According to this model- based approach for the introduction of renewable energy innovations only 2 to 3% of the population of the ‘innovation type’ would like to participate in new developments. This could increase to 15% if the group described as ‘early adopters ‘ would participate as well. As such it will be necessary to further research the possibilities of stimulating sustainable development through ‘joint residents initiatives’. Sustainable development according to the approach of the UN Brundtland Commission (1987), includes both a physical as well a social and sustainable developments places in a durable context: ‘the developments that meet the needs of the present without compromising those of future generations.’ This would require a perfect and sustainable balance of ecological, economic and social interests. Within an urban environment, the restructuring activities (technical quality, the quality of living and quality of life in neighbourhoods and districts), social problem solving (how people interact in social cohesion) and sustainability challenges (environmental, energy -related) as well as the sustainability challenge (now and in the future) are to be the most timely and urgent. The relationships, described by Brundtland between physical, social and sustainable, laid the groundwork to involve the knowledge and experience of ‘residents initiatives’ in the Dutch neighbourhood restructuring challenges, for investigating ‘the potential’ of residents initiating renewable energy in the home environment. As was reflected in the central research question: ‘Under which conditions do social cohesion and sustainable corporate residents initiative influence each other successfully, for the sake of renewable energy in the built environment for living?’ In order to be able to answer the central research question, two lines of research were followed; in addition to research on conditions for social cohesion (a social collective of residents), conditions for residents collectives to invest in renewable energy were investigated. The research methodology included a combination of literature review, case studies at various levels (group discussions, interviews) and research among professionals (group discussions). This included (besides the literature search) all qualitative research to get the motivations and reasons behind ‘residents decisions’ more clear. The above mentioned case studies included both neighbourhoods that are known for the present social cohesion and sustainability realized as a result of ‘residents initiative’. This included the districts IJburg Amsterdam and Hoograven Utrecht, some ecological neighbourhoods in The Netherlands, as well as the GWL site in Amsterdam and ‘City of the Sun’ in Heerhugowaard. The geographic scale on which ‘residents initiatives’ appear, has therewith a part of the research and a component in analyses. Finally, group discussions with professionals regarding the role of resident initiatives, both in urban development (real estate professionals) and energy transition (renewable energy) in the environment (energy professionals) were conducted. This was included to establish the attitude and roles of professionals towards ‘residents initiative’. The conclusion is that three ‘Blocking dilemmas’ further prevent the development of ‘joint residents initiative’ for renewable energy. These ‘Blocking themes’ are: the limited motivation of residents to act sustainably, that social and sustainable ‘residents initiatives’ are not mutual acting together giving start conditions, and the fact that the professionals involved primarily act with a long term view and not short term as residents that generally do. The survey results also provide insight into new perspective for a more significant transition to renewable energy from joint initiative of resident groups. Three ‘Chance Full development opportunities’ may also contribute. These are: mainly the ‘Pull’ conditions motivate residents, residents are willing to follow ‘leaders’ (residents and/or professionals), and social cohesion provides durability on ‘joint residents initiatives’. Involvement and integration of renewable energy through ‘joint residents initiative’ cannot therefore be considered separately from the entire spectrum of sustainable development of energy sources. This because residents (individually and in groups) derive their motivation to improve the quality of life in their home environment rather, both socially and physically, as that on the basis of the renewable energy aspects alone. For a far-reaching transition of ‘residents involvement’, beyond that of the ‘early adopters’, it is not only necessary that professionals and residents are aware of this, leaders (initiating residents or professionals) are needed to start such initiatives. Only when this condition is fulfilled, projects on neighbourhood scale will be successful. The underlying reason is that residents and professionals due to their underlying interests rather act on the scale of the individual property (including the immediate environment) and the scale of the neighbourhood, the city and the region, respectively. Both local and national government can make a substantial contributions by informing citizens on a less fragmented basis, and more so as a part of the viability statement. Furthermore, taken the above aspects in the contract and covenant formation with professional companies will also improve the situation. Above all, professionals will need to listen (and to act in accordance with) to what motivates people in any situation. To obtain a full impression of the ‘Pull’ factors of residents is the first step to a successful transition towards a more significant integration of renewable energy sources in the urban environment in The Netherlands.